IMPACT OF ATTITUDE MODIFICATION METHOD ON STUDENTS’ ATTITUDE TO PRE-MARITAL SEX IN OREDO, EDO STATE, NIGERIA - Igbinosa V.; Lawal K. K; Ikuburuju O.; Abidemi A. (African Journal of Educational Management, 2021)
This study investigated Impact of Attitude Modification Method on Students’ Attitude to Pre-Marital Sex in Oredo Local Government Area, Edo State. To carry out this study, two null hypotheses were formulated to give direction. The sample of the study consisted two hundred (200) randomly selected students from public secondary schools in Oredo L.G.A. Edo State. The instrument used for data collection was a self-developed questionnaire. The data collected were analyzed and the formulated hypotheses were tested using Chi-square statistical methods. All the hypotheses were tested at 0.05 level of significant. The results of the data analysis showed: There is gender difference in the attitude to pre-marital sex among the secondary school students and there will be no significant difference in the students’ attitude to pre-marital sex due to their ages. Based on the findings of the study the following recommendations were made: - School counsellors, guidance services and moral instruction lessons should be strengthened in schools; Efforts should be geared towards avoiding the negative consequences to premarital sex; Young people should be informed to make choices regarding their sexuality. They should be empowered to make decisions that they find most suitable to their situation; Comprehensive Sexual Education should be introduced in schools at all levels; Family structure should be strengthened in Nigeria so that the adolescents can be taught to eschew pre-marital sex before marriage and Sex education should be incorporated into the school’s curriculum from primary to tertiary levels and parents should be encouraged to openly discuss the important topic of sex with their children.